Efficacy of a group intervention program with women victims of gender violence in the framework of contextual therapies - Vaca-Ferrer, Rosario; Ferro Garcia, Rafael; Valero-Aguayo, Luis (Anales de Psicología / Annals of Psychology, 2020)
The goal of this study is to empirically evaluate the efficacy of an intervention program with women victims of gender violence. Specifically, Functional Analytical Psychotherapy has been used, combined with Acceptance and Commitment Therapy, and Behavioral Activation. It has been carried out in group format, during 11 sessions of 2 hours each. A total of 21 women participated (an average of 45 years-old), who had suffered physical violence and/or emotional abuse by their partners, with different degrees and intensity, and at different moments of their lives. An intra-group design with pre-post measures was used. Three treatment groups were carried out in different cities with 6 to 8 women each one. To measure the intervention, the Clinical Outcomes in Routine Evaluation-Outcome Measure (CORE-OM) questionnaire was applied. The results has shown a statistically significant decrease in the severity of discomfort, decreased suicide risk indicators, improved problem behavior inside and outside sessions, and increased openness to others. The usefulness of contextual therapies to improve the quality of life of battered women and their usefulness for application in groups in public institutions are discussed.